High Temporal Variability of Total Organic Carbon in the Deep Northeastern Pacific - Lopez, Chelsi N.; Robert, Marie; Galbraith, Moira; Bercovici, Sarah K.; Orellana, Monica V.; Hansell, Dennis A. (Frontiers in Earth Science, 2020)
The interseasonal and interannual variability of total organic carbon (TOC) was assessed in the deep northeastern Pacific Ocean, an area characterized by high primary production and organic matter export. Samples were collected from throughout the deeper water column (>250 m) seasonally in 2017 and 2018 along the Line P transect, as well as one distribution of dissolved organic carbon (DOC) in spring 2018. High heterogeneity was observed in TOC concentrations at depths greater than 1000 meters, both within seasons (concentration differences of ~2-6 µmol kg-1) and across seasons (~2-12 µmol kg-1), coinciding with changes in fluorescence in the overlying waters. Such observations suggest that biogenic particles sinking from the upper ocean are seasonally delivering observable TOC to depth. The presence of these particles also appeared to contribute to the DOC pool, as suggested by differences in the TOC and DOC distributions in spring 2018. Seasonal TOC net accumulation and removal rates differed between the years: 0.5 and 2.1 µmol kg-1 day-1 (accumulation) and 0.6 and 2.1 µmol kg-1 day-1 (removal) for 2017 and 2018, respectively. The rate estimates indicated that introduction of organic carbon to the bathypelagic occurred at approximately the same rate as removal post-bloom, demonstrating the efficient removal of seasonally-produced organic carbon. High abundances of gelatinous zooplankton in spring 2018, supported by higher abundances of phytoplankton, enhanced the export of organic carbon to the bathypelagic zone during the seasonal bloom, resulting in localized TOC concentrations up to 148 µmol kg-1 in the bathypelagic. These results indicate high variability in bathypelagic TOC concentrations at high latitude, unlike oligotrophic systems.